Single‐Assay Profiling of Nucleosome Occupancy and Chromatin Accessibility. Issue 1 (13th February 2018) - Cook, April; Mieczkowski, Jakub; Tolstorukov, Michael Y.
Abstract: This unit describes a method for determining the accessibility of chromatinized DNA and nucleosome occupancy in the same assay. Enzymatic digestion of chromatin using micrococcal nuclease (MNase) is optimized for liberation, retrieval, and characterization of DNA fragments from chromatin. MNase digestion is performed in a titration series, and the DNA fragments are isolated and sequenced for each individual digest independently. These sequenced fragments are then collectively analyzed in a novel bioinformatics pipeline to produce a metric describing MNase accessibility of chromatin (MACC) and nucleosome occupancy. This approach allows profiling of the entire genome including regions of open and closed chromatin. Moreover, the MACC protocol can be supplemented with a histone immunoprecipitation step to estimate and compare both histone and non‐histone DNA protection components. © 2017 by John Wiley & Sons, Inc.